Mental Health of Migrants in the Covid-19 Pandemic: A Systematic Review - Ebru Akgün Çıtak; Tuğçe Uçgun (Psikiyatride Güncel Yaklaşımlar, 2023)
The Covid-19 pandemic has negatively affected the mental health of individuals due to both the process and the restrictions it imposes. Migrants, especially one of the vulnerable groups, have been adversely affected by the pandemic due to both the difficulties brought by the migration itself and the living conditions unsuitable for Covid-19. All these negative situations caused the migrants to experience psychosocial problems and created a threat in terms of mental health. A limited number of studies have been found in the literature on the psychosocial problems and mental health of migrants. The aim of this study is to review the studies on the evaluation of psychosocial problems and mental health of immigrants during the Covid-19 pandemic and to systematically examine the results of these studies. Systematic searches were conducted in “PubMed”, “Web of Science”, “ScienceDirect” and “Scopus” database with using to ‘migrants, migrant workers, Covid-19 pandemic, mental health, psychosocial issues’ keywords and combinations. Seventeen studies were included in the systematic review. The sample size of the studies varies between 10 and 28.853. As a result of the data, it was determined that the most common psychosocial problems of migrants in the Covid-19 pandemic are depression, anxiety, distress, hopelessness, decrease in socioeconomic level, and social isolation. As a result of the study, it was found that many psychosocial problems that migrants experienced during the Covid-19 pandemic negatively affected their mental health. The evidence determined in this study may guide the psychosocial evaluation of migrants in Covid-19 pandemic.